Carbon Fiber Recycling from Waste CFRPs via Microwave Pyrolysis: Gas Emissions Monitoring and Mechanical Properties of Recovered Carbon Fiber - Kai-Yen Chin; Angus Shiue; Jhu-Lin You; Yi-Jing Wu; Kai-Yi Cheng; Shu-Mei Chang; Yeou-Fong Li; Chao-Heng Tseng; Graham Leggett (Fibers)
Disposing of carbon fiber-reinforced polymers (CFRPs) has become a pressing issue due to their increasing application across various industries. Previous work has focused on removing silane coupling agent residues on recovered carbon fibers via microwave pyrolysis, making them suitable for use in new materials. However, the mechanical performance and structural characteristics of these fibers have not been fully reported. This study investigates the time–temperature curves of CFRPs treated through microwave pyrolysis and analyzes the mechanical and structural properties of silane-controllable recovered carbon fibers. Additionally, emissions—including carbon monoxide, carbon dioxide, and particulate aerosols—were measured using handheld monitors and thermal desorption–gas chromatography/mass spectrometry to determine the composition of fugitive gases around the microwave pyrolysis system. The pyrolysis process at 950 °C, with an additional 1 h holding time, reduced the crystallite size from 0.297 Å to 0.222 Å, significantly enhancing tensile strength (3804 ± 713 MPa) and tensile modulus (200 ± 13 GPa). This study contributes to more sustainable CFRP waste treatment and highlights the potential for reusing high-quality carbon fibers in new applications, enhancing both environmental and worker safety.